2020
DOI: 10.21608/ejfs.2020.22871.1038
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of olive pomace as a source of bioactive compounds in quality improving of toast bread

Abstract: O LIVE oil pomace is produced as by-product with a large quantity during olive oil processing. It is a promising source for polyphenolic compounds and fibers which could be used in food industry. In this work proximate chemical analysis of olive pomace (two-phase olive oil extraction) was studied. Also, seven extracting solvents were tested in extracting the phenolic compounds from the olive pomace (OP). Total phenolic, flavonoids, and flavonols contents of the different extracts were determined. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
2
1
0
Order By: Relevance
“…It can thus be concluded that the addition of OPE did not result in significant sensory changes to the product from the standpoint of consumer acceptance (Figure 7). These results are compatible with those provided by other authors (Lin et al, 2017); (Badawy and Smetanska, 2020); (Cecchi et al, 2019) and (Simsek et al, 2021).…”
Section: Sensory Evaluationsupporting
confidence: 94%
See 2 more Smart Citations
“…It can thus be concluded that the addition of OPE did not result in significant sensory changes to the product from the standpoint of consumer acceptance (Figure 7). These results are compatible with those provided by other authors (Lin et al, 2017); (Badawy and Smetanska, 2020); (Cecchi et al, 2019) and (Simsek et al, 2021).…”
Section: Sensory Evaluationsupporting
confidence: 94%
“…Methanol extraction had significantly (P≤0.05) higher yield (23.40 g/100g DW) than ethanol extraction (22.18 g/100g DW) (Table 2). These results are similar to those obtained by other authors (Badawy and Smetanska, 2020;Gómez-Cruz et al, 2020;Zhao et al, 2022). The selection of solvents could be a crucial factor in the efficiency of extraction of the bioactive compounds from biomass (De Jesus et al, 2020).…”
Section: Yield Of Olive Pomace Extracts (Opes)supporting
confidence: 91%
See 1 more Smart Citation